Be Green to Be Innovative: The Role of Government Subsidies - Xu, Yingbo; Liu, Wei; Pu, Ruihui; Xu, Yonghui (Frontiers in Environmental Science, 2021)
Corporate environmental investment has long been recognized as a non-market strategy that helps secure both economic and social benefits. However, we know much less about how environmental investment affects corporate innovation. We argue that investment in environmental protection is an important source of institutional legitimacy for firms to secure government resources, thus providing financial support for corporate innovation activities. Using a sample of Chinese industrial firms, we find that firms investing more in environmental protection can receive more government subsidies and then have better innovation performance. This study emphasizes the mechanism of government resources, which enriches our understanding of the effect of environmental investment on corporate innovation.